Evaluation of culture media for recovery of Staphylococcus aureus from swimming pools. - Alico, R K (1986)
Several selective media were evaluated for the primary isolation and enumeration of Staphylococcus aureus from halogenated indoor swimming pool waters. Standard plate counts of the viable population and total coliform densities were also determined to ascertain their value as indicator systems. All studies were done with membrane filters. The most selective, accurate, and reliable medium was Vogel-Johnson (VJ) medium supplemented with 0.5% pyruvate. This medium recovered two times more typical colonies than VJ medium alone, and subsequent identification of these well-defined black colonies proved that approximately 80% were S. aureus. The S. aureus recoveries correlated well with halogen levels and bather density use also. In contrast, VJ medium alone was 60% selective for S. aureus, and VJ medium supplemented with catalase did not increase either the percent recovery or the selectivity over that of VJ medium alone. Standard plate counts did not correlate with halogen levels, bather density, or total viable colonies. Coliforms were rarely recovered from indoor pool waters and were not considered to be useful indicators of water quality.